Introduction
The NATURAL NUMBERS are the counting numbers: 1, 2, 3, 4, etc. Based on it, the Mathematical induction is a technique for proving a statement that is asserted about every natural number. By "every", or "all," natural numbers, we mean any one that we name.
Thus,
Mathematical induction is a proof technique. It is a form of direct proof, and it is done based on natural numbers in following steps.
- Define the argument \(P(n)\)
- Prove the argument for \(n=1\)
- Prove the argument for \(n=2\)
- Assume the argument is true for \(n=k\)
- Prove the argument for \(n=k+1\)
Example 1
Prove that (ab)n=anbn is true for every natural number n
Solution
- Step 1 − For n=1,(ab)1=a1nb1=ab, Hence, step 1 is satisfied.
- Step 2-For n=2,(ab)2=(ab)1+1=(ab)1(ab)1=a1b1a1b1=a2b2
- Step 3-For n=3,(ab)3=(ab)2+1=(ab)2(ab)1=a2b2a1b1=a3b3
- Step 4(hypothesis step) − It assumes that the statement is true for the nth iteration (n=k)
- Step 5(Inductive ste) − It proves that a statement is true for the value n=k+1
We have to prove that (ab)k+1=ak+1bk+1
Given,
(ab)k=akbk
or (ab)k (ab)=akbk (ab)
or (ab)k+1=ak+1bk+1
So,
(ab) n=anbn is true for every natural number n.
Sum of first \( n\) natural number
Mathematical Induction Method
Show that sum of first \( n\) natural number is \(\frac{n( n+1 )}{2}\) by induction.
Proof
Step 1 Show that the statement holds for \( n = 1\) .
\( P(1) = 1=1\) (E1)
The result is
\( \frac{n(n+1)}{2}=\frac{1(1+1)}{2}=\frac{1.2}{2}=1\) (F1)
It shows that, (E1=F1), the statement is true for n=1
Step 2 Show that the statement holds for \( n = 2\) .
\( P(2) = 1+2 =3\)(E2)
The result is
\( \frac{n(n+1)}{2}=\frac{2(2+1)}{2}=\frac{2.3}{2}=3\) (F2)
It shows that, (E2=F2), the statement is true for n=2
Step 3 Show that the statement holds for \( n = 3\) .
\( P(3) = 1+2+3=6\)(E3)
The result is
\( \frac{n(n+1)}{2}=\frac{3(3+1)}{2}=\frac{3.4}{2}=6\) (F3)
It shows that, (E3=F3), the statement is true for n=3
Step 4 Assume that the statement holds for \( n = k\)
\( P(k) = 1+2+3+...+k\)
The result is
\( \frac{k(k+1)}{2}\)
We assume that,
\(1+2+3+...+k=\frac{k(k+1)}{2}\) (H)
Step 5 Verify that the statement holds for \( n = k+1\) .
\( P(k+1) = 1+2+3+...+k+(k+1)\)
The result is
\( P(k+1) = 1+2+3+...+k+(k+1)\)
or \(P(k+1) = [1+2+3+...+k]+(k+1)\)
or \(P(k+1) = \frac{k(k+1)}{2}+(k+1) \)
or \(P(k+1) = (k+1)( \frac{k}{2}+1 ) \)
or \(P(k+1) = (k+1)( \frac{k+2}{2} ) \)
or \(P(k+1) = \frac{(k+1)[(k+1 )+1]}{2} \)
or \(P(n) = \frac{n(n+1)}{2} \)
This shows that the statement is true for \( n=k+1\) .
Thus, for any natural number \( n\) , we have,
\( 1+2+3+...+n = \frac{n(n+1)}{2}\)
This completes the proof.
Geometrical Method
चित्रमा दुईवटा 1+2+3+…+8 को योगलाई आयताकार रुपमा प्रस्तुत गरिएको छ। जसमा,
\(S_8=1+2+3+…+8\)
or \(2S_8= \)आयतको क्षेत्रफल
or \(S_8=\frac{1}{2}\) आयतको क्षेत्रफल
or \(S_8=\frac{1}{2}\) लम्बाई x चौडाई
or \(S_8=\frac{1}{2} (8+1) \times 8\)
यसै गरि 1+2+3+…+n हुँद, adding the natural numbers up to n, twice, we get
Sn | =1 | +2 | 3 | +---+ | (n-2) | +(n-1) | +n |
Sn | =n | +(n-1) | +(n-2) | +---+ | +3 | +2 | +1 |
2Sn | =(n+1) | +(n+1) | +(n+1) | +---+ | +(n+1) | +(n+1) | +(n+1) |
2Sn | =n(n+1) | ||||||
Sn | =\(\frac{n(n+1)}{2} \) |
Therefore,
\(S_n= \frac{1}{2} (n+1) \times n \)
or \( S_n= \frac{n(n+1)}{2}\)
Algebraic Method
Show that sum of first \( n\) natural number is \(\frac{n( n+1 )}{2}\) by induction.
Proof
We know that,
\(r^2-(r-1)^2=2r-1\)
Thus, taking the values from r=1,2,...n, and then summing up, we get
Taking r=1 | \(1^2-(1-1)^2=2.1-1\) |
Taking r=2 | \(2^2-(2-1)^2=2.2-1\) |
Taking r=3 | \(3^2-(3-1)^2=2.3-1\) |
Taking r=4 | \(4^2-(4-1)^2=2.4-1\) |
\(\cdots \) | \(\cdots \) |
Taking r=n | \(n^2-(n-1)^2=2.n-1\) |
Summing up r=1 to n | \(n^2=2(1+2+3+..+n)-1.n\) |
As we know, \(S_n=1+2+3+..+n\), so from the sum, we can write
\(2S_n= n^2+n\)
or\(S_n= \frac{n(n+1)}{2}\)
Sum of square of first \( n\) natural number
Mathematical Induction Method
Show that sum of square of first \( n\) natural number is \(\frac{n( n+1 )( 2n+1 )}{6}\) by induction.
Proof
Step 1 Show that the statement holds for \( n = 1\) .
\( P(1) = 1^2=1\) (E1)
The result is
\( \frac{n(n+1)( 2n+1 )}{6}=\frac{1(1+1)( 2.1+1 )}{6}=\frac{1.2.3}{6}=1\) (F1)
It shows that, (E1=F1), the statement is true for n=1
Step 2 Show that the statement holds for \( n = 2\) .
\( P(2) = 1^2+2^2 =5\)(E2)
The result is
\( \frac{n(n+1)( 2n+1 )}{6}=\frac{2(2+1)( 2.2+1 )}{6}=\frac{2.3.5}{6}=5\) (F2)
It shows that, (E2=F2), the statement is true for n=2
Step 3 Show that the statement holds for \( n = 3\) .
\( P(3) = 1^2+2^2+3^2 =12\)(E3)
The result is
\( \frac{n(n+1)( 2n+1 )}{6}=\frac{3(3+1)( 2.3+1 )}{6}=\frac{3.4.7}{6}=14\) (F3)
It shows that, (E3=F3), the statement is true for n=3
Step 4 Assume that the statement holds for \( n = k\)
\( P(k) = 1^2+2^2 +3^2+4^2+…..+k^2\)
The result is
\( \frac{k(k+1)( 2k+1 )}{6}\)
We assume that,
\(1^2+2^2 +3^2+4^2+…..+k^2=\frac{k(k+1)( 2k+1 )}{6}\) (H)
Step 5 Verify that the statement holds for \( n = k+1\) .
\( P(k+1) = 1^2+2^2 +3^2+4^2+…..+k^2+ (k+1)^2\)
The result is
\( P(k+1) = (1^2+2^2 +3^2+4^2+…..+k^2)+ (k+1)^2\)
or \(P(k+1) = \frac{k(k+1)( 2k+1 )}{6}+(k+1)^2\)
or \(P(k+1) = (k+1)\{ \frac{k( 2k+1 )}{6}+(k+1) \}\)
or \(P(k+1) = (k+1)\{ \frac{k( 2k+1 )+6(k+1)}{6} \}\)
or \(P(k+1) = (k+1)\{ \frac{2k^2 +7k+6}{6} \}\)
or \(P(k+1) = (k+1)\{ \frac{( 2k+3 )(k+2)}{6} \}\)
or \(P(k+1) = (k+1)\{ \frac{( 2k+2+1 )(k+1+1)}{6} \}\)
or \(P(k+1) = (k+1)\{ \frac{( 2(k+1)+1 )(( k+1 )+1)}{6} \}\)
or \(P(n) = \frac{n(n+1)( 2n+1 )}{6} \)
This shows that the statement is true for \( n=k+1\) .
Thus, for any natural number \( n\) , we have,
\( 1^2 +2^2 +3^2 +....+n^2 = \frac{n(n+1)( 2n+1 )}{6}\)
This completes the proof.
Geometrical Method
The length of the cube is 1 unit, the volume of cube is 1 cubic unit. In this case, the volume non-shaded region=1 in first figure, the volume of non-shaded region =\(\frac{2}{3}\) in second figure, and the of the volume non-shaded region=\(\frac{1}{2}\) in third figure. Let \( V_n\) be the sum of volume of first \( n^2\) bricks, then
\( V_2 =\frac{1}{3}(2^3 )+\frac{2}{3}(2)+\frac{1}{2}(0+2)
\)
This is shown as below
Also,
\( V_3 =\frac{1}{3}(3^3 )+\frac{2}{3}(3)+\frac{1}{2}(0+2+4)
\)
this is also shown in the figure below
Also
\( V_4 =\frac{1}{3}(4^3 )+\frac{2}{3}(4)+\frac{1}{2}(0+2+4+6)
\)
This is shown in a figure below.
Similarly,
Find the sum of cube of first nnatural number geometrically When we use induction to prove that \(P(n)\) is true for all natural numbers \(n\), our inductive hypothesis is the assumption that \(P(i)\) is true for \(i= 1, 2,...,k\). That is, the inductive hypothesis includes all \(k\) statements \(P(1), P(2),...,P(k)\). Because we can use all \(k\) statements \(P(1), P(2),...,P(k\) true to prove \(P(k+ 1)\), is true. Because of this, some mathematicians prefer to always use strong induction instead of mathematical induction, even when a proof by mathematical induction is easy to compute. Strong induction is sometimes called the second principle of mathematical induction or complete induction. It is defined as below. Show that sum of cube of first n natural number is Sn=\(\left (\frac{n(n+1)}{2} \right )^2 \) Adding, we get
\( V_n=\frac{1}{3}(n^3 )+\frac{2}{3}(n)+\frac{1}{2}[0+2+4+6+2(n-1)] \)
or \( V_n=\frac{1}{3}(n^3 )+\frac{2}{3}(n)+\frac{1}{2}\times 2[0+1+2+3+(n-1)] \)
or \( V_n=\frac{1}{3}(n^3 )+\frac{2}{3}(n)+[1+2+3+(n-1)+n-n ]\)
or \( V_n=\frac{1}{3}(n^3 )+\frac{2}{3}(n)+\frac{n(n+1)}{2}-n \)
or \( V_n=\frac{2n^3 +4n+3{{n}^{2}}+3n-6n}{6}\)
or \( V_n=\frac{2n^3 +3{{n}^{2}}+n}{6}\)
or \( V_n=\frac{n( n+1 )( 2n+1 )}{6}\)
Sum of cube of first \( n\) natural number
Geometrical Method
Let us take sum of first five cubes of natural numbers, viz. \(1^3+2^2+3^3+4^3+5^3\), where
\( 1^3=1, 2^3=2 \times 2^2 ,3^3=3 \times 3^2, 4^3=4 \times 4^2 , 5^3=5 \times 5^2\)
In the figure below
\(1^3+2^2+3^3+4^3+5^3\) are added to from a rectangle
The result is a square of length \(l=\frac{n(n+1)}{2}\) which is in this case \(l=1+2+3+4+5=15\)
Therefore, the sum of cubes of first \(n\) natural number is
\(1^3+2^2+3^3+4^3+5^3+...+n^3\)=Area of square [ length \(l=1+2+3+4+5+...+n\)]
We know that,
\(l=1+2+3+4+5+...+n=\frac{n(n+1)}{2}\)
Therefore
\(1^3+2^2+3^3+4^3+5^3+...+n^3=\) Area of square [ length \(l=\frac{n(n+1)}{2}\)]
or \(1^3+2^2+3^3+4^3+5^3+...+n^3=\left [\frac{n(n+1)}{2} \right ]^2\)
This completes the proof.
Complete Induction
After completing the basis step and the inductive step, state the conclusion, namely that by mathematical induction, P(n) is true for all integers n.
Exercise
Use mathematical induction for the following exercise.
Example 7
Suppose that \(1^3+2^3+3^3+...+n^3\) =Sn, then we start from
\( r^4-(r-1)^4\)
\(=4 r^3- 6 r^2+ 4 r-1\)
Taking r=1
\(1^4-0^4\)
\(=4 \times 1^3- 6 \times 1^2+ 4\times 1-1 \)
Taking r=2
\(2^4-1^4\)
\(=4 \times 2^3- 6 \times 2^2+ 4\times 2-1 \)
Taking r=3
\(3^4-2^4\)
\(=4 \times 3^3- 6 \times 3^2+ 4\times 3-1\)
.............................
............................
............................
Taking r=(n-1)
\((n-1)^4-(n-2)^4\)
\(=4 \times (n-1)^3- 6 \times (n-1)^2+ 4\times (n-1)-n \)
Taking r=n
\(n^4-(n-1)^4\)
\(=4 \times n^3- 6 \times n^2+ 4\times n-1\)
\( n^4=4 (1^3+2^3...+ n^3)- 6 (1^2+2^2+...+ n^2)+ 4(1+2...+n)-n \)
or
\(n^4\)=4 (Sn)- \(6 \frac{n(n+1)(2n+1)}{6}+ 4 \frac{n(n+1)}{2}-n \)
or
4 (Sn)=\( n^4+ n(n+1)(2n+1)- 2 n(n+1)+n \)
or
4Sn= \( n^4+ 2 n^3 +n^2 \)
or
Sn=\( \left (\frac{n(n+1)}{2} \right )^2 \)
No comments:
Post a Comment